Working from home making the new normal work for you - Mangia, Karen (Gildan Audio, 2020)
Master the delicate art of working from home with this comprehensive resource. Working from Home: Making the New Normal Work for You provides listeners with a detailed strategy on how to turn working from home into a powerful career choice. Author and Salesforce executive Karen Mangia teaches listeners how to: build the future of work in any kind of space: ideas for your home office that fit anywhere; create personalized time management routines designed specifically for remote productivity, impact, and balance-even while wearing your sweatpants; deal with Zoom fatigue, burnout, and isolation, via untapped new strategies for connection and team-building, even when the team is remote; and discover how to deliver powerful virtual presentations and build career impact online, with expert communication strategies designed for an online world. Working from Home explains in detail how to turn even the smallest of living spaces into the ideal remote work environment. It comprehensively explores how you can make yourself vital to any organization without ever setting foot in an office building. Because success isn't a location: you can move your career forward from anywhere, if you know how to do it. This book will show you how to embrace the new normal and make sure your career doesn't miss a beat.